Rancang Bangun Mesin Adjustable Pipe Notcher - Abdul Hamid Assidiqi; Tri Andi Setiawan; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2021)
Building construction projects carried out by construction company in Sidoarjo are almost always equipped with handrails to secure the edges of the structural area of the building. The pipe in the project handrail must be notched first so that it can be assembled into a protective fence. Manual pipe repair is still used so that the contour of the resulting pipe is less precise and requires a long process. Base on the problem, it will be made an Adjustable pipe notcher design equipped with dual ragum to help the pipe repair process. Ulrich method will be used in the design concept of adjustbale pipe nocther with problem analysis stage and up to design concept making. Then it will be calculated the required motor power, shaft diameter, bearings. Machine manufacturing includes cutting processes, milling processes, lathe processes, grinding processes, and welding processes. Based on the test results of the machine obtained the results of pipe repair diameter 1.25 inch, 1.5 inch and 2 inch for 4.45 minutes, 6.30 minutes and 9.27 minutes which is faster than the process of manually disuffling pipes that takes 10 minutes, 12 minutes and 15 minutes. The total production cost of making adjustable pipe notcher machine is Rp. 3,421,000.